Opportunities for Implementing Low-Tech Dew and Fog Harvesting Architecture in Indonesia: A Narrative Literature Review - Khamdevi, Muhammar; Riupassa, Robi Dany (MARKA (Media Arsitektur dan Kota) : Jurnal Ilmiah Penelitian, 2024)
The water crisis is affecting the entire world, including Indonesia. Java, Bali, and Nusa Tenggara regions are vulnerable to such disasters. Low-income and traditional communities will be the first to feel the effects. Low-tech dew and fog harvesting buildings have been built in several parts of the world as alternative methods to address water scarcity. This technology necessitates the collaboration of multidisciplinary researchers and practitioners, particularly in architectural science, in the design development of this building. These building design requirements must be tailored to local Indonesian conditions. This study will examine the building opportunities that use this technology in the local Indonesian context, focusing on the potential for the adoption and modification of traditional buildings. This research method employs a narrative literature review of official document data and scientific studies. The study's findings indicate that traditional buildings in Indonesia have a high potential for the use of this technology.